Monozygotic twins with chromosome 22q11 deletion and discordant phenotype. Issue 9 (September 1995) - Goodship, J; Cross, I; Scambler, P; Burn, J
Abstract : We report monozygotic twins concordant for 22q11.2 deletion but discordant for clinical phenotype. Both boys show the typical dysmorphic features with short palpebral fissures, square nasal tip, small mouth, and both have nasal speech, but only one twin had a heart defect. They show that the phenotypic variability seen in this microdeletion syndrome cannot be explained on the basis of genotypic differences alone.